2021
DOI: 10.5796/electrochemistry.21-00076
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Mixing Processes and Properties of Lithium-ion Battery Electrode-slurry

Abstract: The mixing process of electrode-slurry plays an important role in the electrode performance of lithium-ion batteries (LIBs). The dispersion state of conductive materials, such as acetylene black (AB), in the electrode-slurry directly influences the electronic conductivity in the composite electrodes. In this study, the relation between the mixing process of electrode-slurry and the internal resistance of the composite electrode was investigated in combination with the characterization of the electrode-slurries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…We found that the network structure of the conductive material in the electrode-slurry is important for the reduction of internal resistance [22][23][24][25]. Furthermore, the electronic resistance of the composite electrode is reduced by selecting the appropriate conductive material and mixing process [25]. The study demonstrated that AB acts as an effective conductive material and that the mixing process of AB and the active material in a low-viscosity state leads to a good electron conduction network structure in the electrode-slurry.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We found that the network structure of the conductive material in the electrode-slurry is important for the reduction of internal resistance [22][23][24][25]. Furthermore, the electronic resistance of the composite electrode is reduced by selecting the appropriate conductive material and mixing process [25]. The study demonstrated that AB acts as an effective conductive material and that the mixing process of AB and the active material in a low-viscosity state leads to a good electron conduction network structure in the electrode-slurry.…”
Section: Introductionmentioning
confidence: 83%
“…We focused on the electronic resistance of the composite electrode and developed a new method of measuring the electronic conductivity of electrode-slurry. We found that the network structure of the conductive material in the electrode-slurry is important for the reduction of internal resistance [22][23][24][25]. Furthermore, the electronic resistance of the composite electrode is reduced by selecting the appropriate conductive material and mixing process [25].…”
Section: Introductionmentioning
confidence: 93%
“…Particularly, his main concern is electrochemical impedance spectroscopic analysis for practical lithium-ion batteries. [170][171][172][173] Tomokazu FUKUTSUKA is currently a professor at Graduate School of Nagoya University. He was a research associate at Himeji Institute of Technology (currently University of Hyogo) from 2000 to 2007.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…His research interests are energy conversion devices such as lithium-ion batteries and next-generation rechargeable batteries (all-solid-state Li, Na, Mg, and F) and fundamental research and new material development are undergoing. He has published over 100 papers, [174][175][176][177][178] contributed his papers with many coauthors in Electrochemistry during his research experiences, 173,179,180 and one of them has received Excellent Paper Award of ECSJ in 2021. 60 Takeshi ABE is currently a professor at Graduate School of Kyoto University.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…Carbon is one of the key components in electrochemical energy conversion and storage systems, such as lithium-ion batteries, [1][2][3][4][5][6] electrochemical capacitors, [7][8][9][10][11][12][13][14][15] polymer electrolyte fuel cells (PEMFCs), [16][17][18][19][20][21][22][23] and metal-air secondary batteries (MABs). [24][25][26][27][28][29][30][31] However, carbon materials suffer from electrochemical oxidation; that is, carbon corrosion occurs in aqueous electrolytes at high anodic potentials, where many important electrochemical reactions, including the oxygen evolution reaction (OER), transpire.…”
Section: Introductionmentioning
confidence: 99%